EFEKTIVITAS MEDIA PEMBELAJARAN POWER POINT INTERAKTIF BERBASIS INKUIRI TERBIMBING PADA MATERI HIDROLISIS GARAM TERHADAP HASIL BELAJAR PESERTA DIDIK MAN 2 KOTA PADANG - Hana Nurfalah; Syamsi Aini (Prima Magistra: Jurnal Ilmiah Kependidikan, 2023)
Salt hydrolysis material is one of the chemical materials that is abstract and difficult for students to understand. Therefore, learning media are needed that are able to increase understanding by using interactive power-point. The purpose of this study was to test the effectiveness of the use of guided inquiry-based interactive power-point learning media on salt hydrolysis material on the learning outcomes of class XI students at MAN 2 Padang City. This experimental research uses the Nonequivalent Control-Group Design. The population in this study were all students of class XI IPA at MAN 2 Padang City consisting of 9 classes in the even semester of the 2022/2023 academic year. The sampling technique was carried out by purposive sampling method. The research instrument was in the form of a multiple choice test that has been tested for validity, reliability, item discriminating power, and a good index of difficulty. Data were analyzed using the n-gain test and hypothesis testing with independent sample t-test. The results of the data analysis show that the experimental class has a higher n-gain compared to the control class in the medium category. In addition, the results of the hypothesis test show a significance value (sig) of less than 0.05, so that H1 is accepted and H0 is rejected. From the results of the data analysis, it can be concluded that the use of guided inquiry-based interactive Power-Point learning media on salt hydrolysis material is effective in improving student learning outcomes.